Advances in aquaculture hatchery technology - Allan, Geoff L. (Geoffrey Laurence); Burnell, Gavin (Oxford : Woodhead, 2013)
For seafood production to meet expected demand from a growing global population, many more millions of tons of seafood will need to be produced. The expectations for increased product from capture fisheries is limited, so this rise in production will have to come from aquaculture, one of the fastest growing food producing sectors in the world. A primary constraint to the continuing growth of aquaculture is the supply of juveniles from hatcheries --
Includes bibliographical references and index.
Keywords: Aquaculture -- Research; Fishes -- Breeding; Fish hatcheries; Fishery resources -- Hatchery vs. wild stocks; Fishery management; Biotechnology